2018
DOI: 10.1016/j.mce.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone signaling: An information theoretic approach

Abstract: Gonadotropin-releasing hormone (GnRH) is a peptide hormone that mediates central control of reproduction, acting via G-protein coupled receptors that are primarily G coupled and mediate GnRH effects on the synthesis and secretion of luteinizing hormone and follicle-stimulating hormone. A great deal is known about the GnRH receptor signaling network but GnRH is secreted in short pulses and much less is known about how gonadotropes decode this pulsatile signal. Similarly, single cell measures reveal considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
1
12
0
1
Order By: Relevance
“…These studies however, along with advances in neural information theory, underscored the importance of interneuronal communication in the brain and confirmed, in part, that no specific region of the brain was entirely responsible for the behavioral manifestations of mood disorders. [ 6–10 ] Instead, a subset of several active brain nuclei appeared to be required where the loci could vary among patients. As a result, methods that employed whole brain activity via imaging studies such as functional positronic emission tomography (fPET), nuclear magnetic resonance spectrometry and indeed, re‐visitation of electroencephalography led to the confirmation that numerous regions rather than a single locus of the brain were associated with the onset of affective disorders.…”
Section: History Of the Physiology And Pathology Of Affective Disordersmentioning
confidence: 99%
“…These studies however, along with advances in neural information theory, underscored the importance of interneuronal communication in the brain and confirmed, in part, that no specific region of the brain was entirely responsible for the behavioral manifestations of mood disorders. [ 6–10 ] Instead, a subset of several active brain nuclei appeared to be required where the loci could vary among patients. As a result, methods that employed whole brain activity via imaging studies such as functional positronic emission tomography (fPET), nuclear magnetic resonance spectrometry and indeed, re‐visitation of electroencephalography led to the confirmation that numerous regions rather than a single locus of the brain were associated with the onset of affective disorders.…”
Section: History Of the Physiology And Pathology Of Affective Disordersmentioning
confidence: 99%
“…Ligand-stimulated GnRHR triggers multiple signaling pathways through diverse Gα proteins. Among the G protein pathways, the activated Gαq mediates reproductive function in pituitary cells and is considered as the primary pathway for GnRHR (7)(8)(9). It has been also reported that GnRH analogs possess inhibitory effects in several cancer cell types via Gαi protein.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the GPCR families, GnRHR transduces the intracellular GPCR signals via multiple heterotrimeric G proteins (5,6). In pituitary gonadotropes, GnRHR primarily interacts with Gαq and exerts reproductive effects such as synthesis and secretion of pituitary gonadotropin hormones, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an original approach tackled the question from a signal engineering viewpoint, applying the concepts of information transfer (Voliotis et al, 2018). The main interest is to take advantage of the information processing properties resulting from the heterogeneity of responses within a cell population.…”
Section: Gnrh Signaling In Gonadotrophsmentioning
confidence: 99%